Optimization of microwave absorption properties of C/NiP microfiber composites. Issue 6 (15th March 2021) - Wei, Yupeng; Lin, Jingpeng; Jiang, Tiantian; Li, Linqi; Zhong, Kangyou; Zhang, Junwei; Peng, Yong
Abstract: Core-shell C/NiP microfiber composites were fabricated via electroless plating in this work. Their microstructure and electromagnetic properties were adjusted by annealing treatment and different phosphorus (P) content in the NiP coating. The C/NiP microfibers composites with 6 wt % P content in the NiP coating annealed at 300 °C remarkably owns −46.7 dB strong reflection loss at 10.0 GHz with the thickness of 2.0 mm, and the effective bandwidth (RL ≤ −10 dB) reaches 8.1 GHz (3.1–11.2 GHz). This work shows that the annealing conditions and different P concentrations in the coating layers for C/NiP microfibers composites are the effective way to optimize the electromagnetic wave absorption performance.